If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -22t + 72 = 35 Reorder the terms: 72 + -22t = 35 Solving 72 + -22t = 35 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-72' to each side of the equation. 72 + -72 + -22t = 35 + -72 Combine like terms: 72 + -72 = 0 0 + -22t = 35 + -72 -22t = 35 + -72 Combine like terms: 35 + -72 = -37 -22t = -37 Divide each side by '-22'. t = 1.681818182 Simplifying t = 1.681818182
| -6u-7=-3u+17 | | 4x+9y=96 | | -52s-66+66=105+66 | | 15x=330 | | 3=2+x/2 | | 5x+5y=40 | | 4.4v+4.9=4.3v+5.2 | | -52s+-66=105 | | 5.8w-4.8w+1.7=-9.2 | | -(4x-2)=-4x+1 | | 17=-5t-14 | | y^3-11y^2+30y=0 | | x^2-10x-85=0 | | 25x^2-40x-16=0 | | 2x^4+5x^3+29x^2+80x-48=0 | | 1+8x^2-7x=2x^2+1-2x | | 2.6*1/w=3.5 | | 25r^2-4r=0 | | 2m-8=5m | | -16t^2+24t+40=0 | | (x+1)(3x+2)=24 | | 12+1+7-13=0 | | 5x+3=-15 | | x/2-2(1-x)=3 | | 20-8/2 | | 3x^2-13x-40=0 | | Y=60x+166 | | 6x(x)-10x=2 | | 14x=19y | | 2+t(-6t)-6=2 | | 12n^2-55n-25=0 | | 1.5=v+3/4 |